DC generation from peripheral blood mononuclear cells in patients with chronic myeloid leukemia: Influence of interferons on DC yield and functional properties. Issue 5 (3rd May 2016) - Flörcken, Anne; Kopp, Joachim; Kölsch, Uwe; Meisel, Christian; Dörken, Bernd; Pezzutto, Antonio; Westermann, Jörg
ABSTRACT: In Chronic Myeloid Leukemia (CML), standard treatment consists of modern tyrosine-kinase inhibitors (TKI). Nevertheless, there is evidence that immune responses against leukemia-associated antigens (LAA) may play an important role in disease control. Dendritic cell (DC)- based immunotherapy is able to induce T cell responses against LAA and might therefore pose an interesting therapeutic option in CML, especially in the setting of minimal residual disease (MRD). GMP production of DC for clinical vaccination remains a time- and cost- intensive procedure and standardized DC generation is warranted. We asked whether maturation-induction with IFN-γ and IFN-α has an influence on functional properties of DC derived from peripheral blood mononuclear cells (PBMC) in CML patients. Monocyte-derived DC from healthy donors and from patients with CML were analyzed after maturation-induction with our TNF-α-containing standard cytokine cocktail with or without addition of IFN-α and/or IFN-γ. Our results confirm that the addition of IFN-γ leads to enhanced IL-12 secretion in healthy donors. In contrast, in CML patients, IFN-γ was not able to increase IL-12 secretion, possibly due to a higher degree of cell adherence and lower cell yield during the cell culture. Our data suggest, that- in contrast to healthy donors-, additional interferons are not beneficial for maturation induction during large-scale DC production in patients with CML.